2006
DOI: 10.1021/jp065139w
|View full text |Cite
|
Sign up to set email alerts
|

Proton Antenna Effect of the γ-Cyclodextrin Outer Surface, Measured by Excited State Proton Transfer

Abstract: The reversible proton dissociation and geminate recombination of the common photoacid, 8-hydroxypyrene-1,3,6-trisulfonate (pyranine), either in dilute aqueous solution or when forming a complex with gamma-cyclodextrin (gamma-CD), has been studied by time-resolved fluorescence spectroscopy and supplemented by molecular modeling and dynamics simulations. We find that the dissociation rate of the proton from the excited molecule was decreased to about approximately 50% of its value in water, while the rate of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 59 publications
5
35
0
Order By: Relevance
“…96 However, when pyranine is encapsulated in a cyclodextrin cavity the ESPT exhibits an additional slow component at the B1500 ps time scale. 97,98 Similar retardation is also observed inside a P123-CTAC aggregate. 99 Proton transfer involves primarily three stepsinitial proton transfer, recombination of the ion pair and dissociation of the ion pair.…”
Section: Implications Of Slow Biological Water In Polar Reactionssupporting
confidence: 69%
“…96 However, when pyranine is encapsulated in a cyclodextrin cavity the ESPT exhibits an additional slow component at the B1500 ps time scale. 97,98 Similar retardation is also observed inside a P123-CTAC aggregate. 99 Proton transfer involves primarily three stepsinitial proton transfer, recombination of the ion pair and dissociation of the ion pair.…”
Section: Implications Of Slow Biological Water In Polar Reactionssupporting
confidence: 69%
“…Huppert et al 5 studied ESPT of a similar molecule in AOT microemulsion and considered a diffusion model introduced by Agmon. Most recently, several groups including us applied femtosecond spectroscopy to study ultrafast ESPT of HPTS in other nanoconfined systems such as cyclodextrins [14][15][16][17][18][19] and polymer-surfactant aggregates. 34 They reported that the rate of ESPT increases gradually on addition of water.…”
Section: Introductionmentioning
confidence: 99%
“…In neat water,t he absorption spectra shows only as ingle prominentp eak at 404 nm, whichi sa ttributed to the protonated form of the dye, and is consistent with previously reported ground-statea bsorption spectra for HPTS in water. [40,57,58] The presence of only one absorption band at all compositions of DMSO/water mixturess uggestst he existence of only the protonated form of HPTS at all compositions.…”
Section: Ground-statea Bsorption Measurementsmentioning
confidence: 99%